KEBIJAKAN PENGADAAN BARANG/JASA METODE PENUNJUKAN LANGSUNG BADAN USAHA MILIK NEGERA BERDASARKAN PERATURAN BUMN NOMOR PER-2/MBU/03/2023 - Rosisca, Napoleon Forte; Ratnawati, Elfrifa; Sumanto, Listyowati (Ensiklopedia of Journal, 2025)
Abstract: This journal analyzes the business competition legal aspects of Direct Appointments through synergies between State-Owned Enterprises (BUMN) in the procurement of goods/services. In an effort to drive economic growth and meet societal needs, (BUMN) often delegate part or all of the procurement work to third parties. This Direct Appointment aims to improve operational efficiency and effectiveness but also poses challenges related to business competition violations and potential corruption. Using the Legal System theory approach, this study identifies factors driving (BUMN) synergies and formulates strategies to prevent potential violations. Public participation and effective oversight are proposed as mitigation steps to ensure a transparent, fair, and accountable procurement process. The research findings are expected to provide insights for developing best practices and policies that support efficient procurement of goods/services while adhering to the applicable legal framework.Keywords: Procurement, Direct Appointment, Business Competition